Contribution of continuously stable sediment input to the formation of the Pearl River delta since the middle Holocene. (10th October 2021) - Qiao, Yansong; Liu, Jianguo; Cao, Li; Rahaman Khan, Md Hafijur; Xu, Xudong; Tan, Long
Abstract: Pearl River sediments have been reported to have changed greatly in composition due to the impact of human activities on erosion and landscapes in southern China since 2500 years BP. Here, sediments from four cores (PRD-1, PRD-3, PRD-6 and PRD-7) from the Pearl River Delta (PRD) were collected for high-density clay mineral analyses to determine the vertical variations in clay mineral compositions since the middle Holocene. The results showed that the clay mineral compositions of these four cores remained constant. In the PRD, the clay mineral assemblage dominantly consists of illite and kaolinite (averaging more than 85%), with smaller amounts of chlorite (averaging 10%) and scarce smectite (averaging 1%). The stable clay mineral assemblages in the PRD confirm that the clay mineral compositions of the sediments continuously supplied by the Pearl River have not changed. However, the smectite percentage in core PRD-7 increased by 7% downward from a depth of 12.4 m, which was correlated with the weathering of local volcanic materials and sediment transport in the east of the Pearl River under the influence of the Guangdong coastal current in winter. The stable clay mineral compositions in the core sediments indicate that the Pearl River sediments have accumulated naturally in the PRD instead of under the influence of human activities, which would have altered the compositions of the core sediments.